Characterization of cenospheres from Malaysian coal generated power plants: Jimah, Kapar and Manjung - Salmia Beddu; Teh Sabariah Abd Manan; Mahyun Mohd Zainoodin; Nur Liyana Mohd Kamal; Affiani Machmudah; Saba Yavari; Daud Mohamad; Zarina Itam; Agusril Syamsir; Fadzli Mohamed Nazri; Yee Hooi Min; Warid Wazien Ahmad Zailani (Fakulti Kejuruteraan ,UKM,Bangi., 2022)
Cenosphere is a component of fly ash (FA) and has been used as part of sustainable material in wastewater treatment, automotive, ceramic, and construction industries due to its properties. This research presents the first study on characterization of cenospheres from Malaysian power plants namely Jimah, Kapar and Manjung. The characterization was conducted via X-ray fluorescence (XRF), particle size analyzer (PSA), X-ray diffraction (XRD), and scanning electron microscopy (SEM). The XRF analysis consisted of oxides elements ranged from 14.70 to 22.63% (aluminum oxide, Al2 O3 ), 3.78 to 13.44% (calcium oxide, CaO), 34.73 to 57.67% (silicon dioxide, SiO2 ), 0.42 to 1.07% (sulphur trioxide, SO3 ), 9.09 to 24.92% (iron oxide, Fe2 O3 ), 3.62 to 3.67% (potassium oxide, K2 O), 1.76 to 4.24% (titanium oxide, TiO2 ) and 0.16 to 0.93% (magnesium oxide, MgO). The classifications of cementitious materials by American Standard of Testing Materials were Class F (Jimah, Kapar) and Class C (Manjung). The classification represents the quality and capability of cementitious materials as cement replacement material, additive, and filler in concrete mix. The sizes of cenospheres were Kapar > Jimah > Manjung. The sizes of cenosphere were found to be larger than FA (Jimah: 2.720-49.21 µm, Kapar: 5.069-98.29 µm, Manjung: 1.084-3.986 µm). Cenospheres contained quarts (Jimah, Kapar, Manjung: 26°) and silicates (Kapar, Manjung: 45°). Ferrospheres, cenospheres, aluminosilicate-spheres, plerospheres and carbon fragments were observed. The cenosphere from Manjung showed high quality as cement replacement material, additive, and filler with 13.44% of CaO.